Defining and measuring nature : the make of all things - Williams, Jeffrey H. (Jeffrey Huw), 1956- (IOP ebooks. 2020 collection., 2020)
Measurement forms an essential part of our view of the world. Our world is measured and calibrated, and we are all subject to the tyranny of these numbers. In this updated and extended edition, Jeffrey Huw Williams outlines the history of measurement; particularly of the International System of units (SI). Since the previous edition, the base units of the SI have been redefined; realising a 150-year-old dream for a measurement system based on unchanging, fundamental quantities of nature. This change has created a new SI, a Quantum-SI, which will significantly change the way we look at nature in a quantitative manner, and greatly facilitate the advance of science.